Penerapan Metode Perbandingan Dempster-Shafer dengan Certainty Factor pada Aplikasi Sistem Pakar Deteksi Dini Penyakit Alzheimer pada Lansia Berbasis Web - Mohamad Aldjawad; Septi Andryana; Andrianingsih Andrianingsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Alzheimer's is a dementia disease associated with changes in protein in the brain. According to WHO, in 2010 there were 35.6 million people suffering from dementia. People with dementia are usually the elderly. Due to the lack of awareness, information, and knowledge about Alzheimer's disease, an expert system was created using the Dempster-Shafer comparison method with Certainty Factors to assist in early detection of the disease. The results of this study are, there is a final value of the diagnostic results using the Certainty Factor method of 56% while using the Dempster-Shafer method of 54.5%.